2018
DOI: 10.1155/2018/4606791
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble-Mediated Ultrasound Outweighs Low-Intensity Pulsed Ultrasound on Osteogenesis and Neovascularization in a Rabbit Model of Steroid-Associated Osteonecrosis

Abstract: Microbubbles magnify the acoustic pressure of low-intensity pulsed ultrasound (LIPUS) and may enhance its bioeffect for diagnostic and therapeutic purposes. This study compared the effect of this novel microbubble-mediated ultrasound (MUS) with that of the traditional LIPUS on osteogenesis and neovascularization in a rabbit model of steroid-associated osteonecrosis. We hypothesized that MUS might outweigh LIPUS on promoting osteogenesis and neovascularization in steroid-associated osteonecrosis. The bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…7E). Several other studies have demonstrated that the application of compressive forces on bone enhances the mineral apposition rate (57,58). Furthermore, our reported mineral apposition rates are in agreement with other studies conducted in rabbit models (57).…”
Section: Mechanical and Chemical Properties Of The Tiger Graft May Enhancesupporting
confidence: 92%
“…7E). Several other studies have demonstrated that the application of compressive forces on bone enhances the mineral apposition rate (57,58). Furthermore, our reported mineral apposition rates are in agreement with other studies conducted in rabbit models (57).…”
Section: Mechanical and Chemical Properties Of The Tiger Graft May Enhancesupporting
confidence: 92%
“…Gas filled microbubbles can amplify the sound pressure and enhance the biological effects of ultrasound, improving the therapeutic effect of LIPUS [21][22][23]. The ultrasonic pulse produces volume pulsation of the microbubbles and generate fluid microflow around the microbubbles, resulting in local shear force on the cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding possible clinical translation of the present research, LIPUS may be effective as a sole therapeutic tool or combined with another therapeutic approach such as microbubbles, which has been reported to enhance the LIPUS effects on cell proliferation and differentiation [75][76][77] and neovascularisation, 78 for stem cell therapy and tis-sue engineering approaches in the regenerative medicine. More specifically related to the present study, the LIPUSinduced cell proliferation of neural stem cells would benefit nerve repair and regeneration approaches like induction of nerve supply for regenerative endodontic treatment and management of traumatic nerve injuries.…”
Section: Discussionmentioning
confidence: 99%